Analisis Parameter Mesin Spot Welding Terhadap Kekuatan Sambungan Las Pada Komponen Grill Diffuser - Ismail, Nur Irfan; Saleh, Moch. (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to determine the effect of welding parameters (time 1.8 seconds, 2 seconds, 2.5 seconds and current 80 kA, 90 kA, 100 kA) on the spot welding process. Knowing the tensile strength of the joints resulting from spot welding and knowing the most optimal time and current conditions in the spot welding process. In this study using a plate thickness of 0.5 mm. The type of research used is experimental research. The results of this study indicate that variations in welding time with current affect the tensile strength. The highest tensile strength is at 2 seconds with a current of 100 kA, namely: 150psi while the lowest tensile strength is at 1.8 seconds with a current of 80 kA, which is equal to: 50psi. This means that the higher the current voltage and the longer the welding time, the the tensile stress strength is also greater, and if the time is not fixed then the welding results will be damaged.